2015
DOI: 10.4172/2324-8602.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Metabolism Biomarkers and Health Related Quality of Life in Pulmonary Arterial Hypertension

Abstract: Objectives The goal of this study was to investigate the association between collagen metabolism biomarkers and health related quality of life (HRQoL) in PAH patients. Methods We prospectively enrolled 68 stable idiopathic, anorexigen-associated, and hereditary PAH subjects and 37 healthy controls. Serum samples were analyzed for N-terminal propeptide of type III procollagen (PIIINP), c-terminal telopeptide of collagen type I (CITP), matrix metalloproteinase 9 (MMP-9) and tissue inhibitor of metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…21 We have also shown that PIIINP is strongly related to health-related quality of life scores in PAH patients, further suggestive of its usefulness as a determinant or confirmation of disease severity. 22 Recently, we published results of a cross-over placebo-controlled clinical trial of PAH patients that received spironolactone and placebo in a randomized order for a minimum of eight weeks. 23 The primary objective of the study was to detect changes in collagen biomarker levels in this population, specifically looking at PIINP levels.…”
Section: Discussionmentioning
confidence: 99%
“…21 We have also shown that PIIINP is strongly related to health-related quality of life scores in PAH patients, further suggestive of its usefulness as a determinant or confirmation of disease severity. 22 Recently, we published results of a cross-over placebo-controlled clinical trial of PAH patients that received spironolactone and placebo in a randomized order for a minimum of eight weeks. 23 The primary objective of the study was to detect changes in collagen biomarker levels in this population, specifically looking at PIINP levels.…”
Section: Discussionmentioning
confidence: 99%
“…The joint subclinical elevation of C-reactive protein and interleukin-6 in plasma was associated with lower HRQoL in the general population [19]. HRQoL scores were strongly related to N-terminal propeptide of type III procollagen in the serum of pulmonary arterial hypertension patients [8]. Elevated baseline serum troponin T levels were independently associated with deterioration in the physical domains of HRQoL in hemodialysis patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been reported that biomarkers, such as interleukin-4RA rs 1805010 [6], insulin-like growth factor-1 [7], and N-terminal propeptide of type III procollagen [8], were associated with HRQoL. Although it is conceivable that the use of biomarkers might help to estimate HRQoL objectively, few studies have explored biomarkers for OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ECM proteins in the microenvironment regulate a variety of processes, such as proliferation, migration, apoptosis, and the response to cellular signaling stimulation [14]. Vascular remodeling in PAH is characterized by the growth of neointimal lesions containing SMCs expressing ECM genes to contribute to abnormal elastic assembly and collagen deposition [15][16][17][18]. Elastic fibers are comprised of an insoluble elastin core and the surrounding mantle of the microfibrillar scaffold, deposition and integration of tropoelastin monomers into the scaffold, and cross-linking of the monomers to form an insoluble, functional polymer [16].…”
Section: Introductionmentioning
confidence: 99%
“…Increased activity of this collagen precedes the development of PAH and accompanies its progression. When the activity of these elastases was inhibited in a variety of rodent models, studies report attenuating both the hemodynamic and structural features associated with PAH [17,18,30]. Furthermore, studies have shown that the elastase activity can also induce regression of PAH by causing apoptosis of SMCs [17,18].…”
Section: Introductionmentioning
confidence: 99%